2005
DOI: 10.1080/00016470510030661
|View full text |Cite
|
Sign up to set email alerts
|

Changed gait pattern in patients with total knee arthroplasty but minimal influence of tibial insert design

Abstract: In patients with a similar degree of degenerative joint disease and within the limits of the constraints offered by the prostheses under study, the choice of joint area constraint has little influence on the gait pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 28 publications
2
39
1
1
Order By: Relevance
“…This marker set was a modification of Helen Hayes marker set 12 and been used previously by our group. [13][14][15] The marker positions were partly chosen to limit the effect of subcutaneous fat. The room coordinate system was defined with one axis in the direction of walking and parallel to the floor.…”
Section: Methodsmentioning
confidence: 99%
“…This marker set was a modification of Helen Hayes marker set 12 and been used previously by our group. [13][14][15] The marker positions were partly chosen to limit the effect of subcutaneous fat. The room coordinate system was defined with one axis in the direction of walking and parallel to the floor.…”
Section: Methodsmentioning
confidence: 99%
“…This is congruent with our study, with notable variability present in both groups. No major differences in the studied parameters of the gait cycle were determined by the femoral design, as seen for the tibia design [26]. However, TKA patients showed a slower gait [26], but the speed during the swing phase of the contralateral limb in our series was better (expressed as % of normal values) in the SR group than in the MR group.…”
Section: Discussionmentioning
confidence: 52%
“…Previous work using parameterization analyses have also found decreased hip extension angles in TKA subjects compared to a control group [12,19]. Saari et al (2005) indicated that abnormal flexion and extension of the knee in TKA subjects might cause reduced hip extension in order to maintain balance during walking.…”
Section: Discussionmentioning
confidence: 99%
“…Saari et al (2005) indicated that abnormal flexion and extension of the knee in TKA subjects might cause reduced hip extension in order to maintain balance during walking. However, our results indicate that reduced hip extension occurs with no significant differences in knee flexion/extension angles between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation